Perlindungan Hukum Terhadap Konsumen Atas Kenaikan Harga Minyak Goreng Yang Dilakukan Oleh Pelaku Usaha Toko di Kecamatan Sabu Barat Kabupaten Sabu Raijua - Rona Pili Mangngi; Agustinus Hedewata; Darius Mauritsius (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The increase in cooking oil as a staple food is certainly detrimental to consumers, especially consumers from the lower middle class, after the problem of scarcity of cooking oil occurred in Indonesia and various policies to adjust the price of cooking oil carried out by the government, provide evidence that the urgency of the price of cooking oil has an impact on society. This research aims to find out and explain the causes of the increase in cooking oil prices carried out by shop entrepreneurs in West Sabu sub-district, Sabu Raijua Regency. The research method used is that this research is included in empirical legal research, namely a legal research method that attempts to see the law in a real sense or can be said to see, examine how law works in society, which then uses a research approach, a qualitative type of approach. The research results show that legal protection for consumers can be carried out by resolving disputes in court and outside of court. Every consumer who is harmed can sue business actors through institutions tasked with resolving disputes between consumers and business actors or through courts within the general court environment and the government also plays an important role in efforts to protect consumers legally. The form of consumer protection provided is by issuing laws and government regulations, where the implementation of statutory regulations is then carried out by supervising the implementation of these regulationsto be able to socialize it to the public and there is also a need for supervision carried out by the government on business actors.